DETERMINAN ANEMIA PADA IBU HAMIL BERDASARKAN PERAN STATUS SOSIAL DAN KEPATUHAN MENGONSUMSI SUPLEMENTASI ZAT BESI DI PUSKESMAS SEI PANAS KOTA BATAM TAHUN 2025 - Acholder Tahi Perdoman; Muhammad Rifki; Alya Caprina Risandi (Zona Kedokteran: Program Studi Pendidikan Dokter Universitas Batam, 2026)
ABSTRACT Background: Anemia in pregnant women remains a public health problem globally (>35%) and in Indonesia (27.7%), including in Batam City. Social status, represented by education and occupation, as well as adherence to iron supplementation, is suspected to play a role in the occurrence of anemia. This study aims to analyze the association between education, occupation, and adherence to iron supplementation and to identify the most dominant factor related to anemia among pregnant women at the Sei Panas Public Health Center, Batam City. Methods: This analytic observational study with a cross-sectional design used secondary data obtained from medical records and the Maternal and Child Health (MCH) handbook of pregnant women. Data were analyzed using univariate analysis, bivariate analysis with the Chi-Square test, and multivariate analysis using logistic regression with a significance level of p<0.05. Results: A total of 43 respondents (50.6%) were anemic. Education (p=0.048), occupation (p=0.037), and adherence to iron supplementation (p<0.001) were significantly associated with anemia in the bivariate analysis. In multivariate analysis, adherence to iron supplementation was the most dominant factor (p<0.001; OR=0.014; 95% CI: 0.003–0.075). Conclusion: Adherence to iron supplementation was the most influential determinant of anemia among pregnant women. Strengthening adherence should be prioritized in anemia prevention strategies. Keywords: Anemia, Pregnant Women, Education, Occupation, Iron Supplementation Adherence